Diversity and Inclusion Working Group: Beyond the IFAC Statement of Values. Issue 39 (2022) - O'Neill, Brenda; Doyle-Kent, Mary; Stapleton, Larry; Bula-Bunjaku, Ines; Shanahan, Breda Walsh
Abstract: As set out in 2021, the profile of the International Federation of Automatic and Control (IFAC) has been evolving in the area of Diversity and Inclusion (O'Neill et al, 2021). The paper presented by O'Neill et al, 2021 raised the profile of D&I within IFAC. Momentum was gained with the statement of values in the process of being adopted by the IFAC D&I Committee. The original contribution of this paper is that it details some of the solid positive progress made within IFAC in the interests of D&I since then. As with all change, when there is a strategy that is well communicated to the organization, then it is more likely to have a successful outcome. Kotter and Schlesinger discuss a systematic way to select an organizational strategy with a set of specific approaches for implementing an organizational change effort (Kotter, J. P. and Schlesinger, L. A. 2008). Progress is being made but change is slow. This paper outlines progress to date and speaks to future possibilities and connecting with other large groups such as the IEEE to see how they explore the diversity and inclusion potential within their organization as a means of moving forward. It aligns with the United Nations Sustainable Development goal 5 Gender Equality. It presents a leadership opportunity for IFAC as an organization. Finally, this paper acts as an opportunity to open the discussion and be more inclusive. Inputs are sought rather like a green paper which could potentially lead to a policy document.